Effects of modified atmosphere on microbial incidence on cauliflower seeds - P.R. KUMAR,; S.N. SINHA,; S.K. LAL,; S. S. SINGH,; ANUJA GUPTA, (Seed Research, 2026)
The modified atmosphere (MA) containing 20 percent CO, and 2 percent O, is capable of controlling the incidence of seed microflora (fungal infestation) in cauliflower seeds. At the same time, low seed moisture contents kept seed borne microflora low, making the modified atmosphere more effective. Hence, it was concluded that hypercarbic atmosphere (20 percent CO₂) compounded with hypoxic condition (2 percent O₂) is highly efficient in controlling fungal infestation in cauliflower seeds during storage. However, an increase in amount of Aspergillus spp. as well as Penicillium spp. in modified atmospheres was noticed.